Nanocomposite Ag:TiN thin films for dry biopotential electrodes - Pedrosa, P. (2013)
Silver-added titanium nitride (Ag:TiN) thin films were deposited by DC reactive sputtering with Ag contents ranging from 0 to ∼50 at.% on silicon and glass substrates, aiming at studying their potential application as bio-electrodes. The coatings were characterised regarding their composition, morphology and structure, and their influence on the variation of the electrical resistivity and thermal properties. The sputtered films’ behaviour was consistently divided into three main zones, defined mainly by the amount of Ag incorporated and the corresponding changes in the structural and morphological features, which affected both the electrical and thermal response of the films. With increasing Ag concentration, the coatings evolve from a nitride/compound-like behaviour to a metallic-like one. Resistivity values suffer a strong decrease due to the increase of compactness of the coatings and the formation of highly conductive Ag phases, counterbalancing the grain size decrease effects promoted by the hindered growth of the crystalline TiN phases. In good agreement with the electrical resistivity evolution, a similar trend was found in the effusivity values, reflecting a significant degradation of the heat conduction mechanisms in the films as the silver content was increased.